1982 3rd Ascope Laboratories Test Correlation Programme On C.F.R. Engine - Bustani Mustafa; E Jasjfi (Testing Center for Oil and Gas LEMIGAS, 1983)
During the 2nd Workshup on the ASCOPE Laboratory Test Correlation Programme which was, held in Kuala Lumpur 17 - 18 August 1981, the following consensus was reached among participating laboratories : • The frequency of the correlation test programme should be increased to twice a year. • Testing should be carried out at the same day and time specified by the Programme coordinator. • Testing should be carried out according to the same procedure (bracketing Method). Member countries taking part in this correlation programme are Indonesia as coordinator with seven laboratories participating, Malaysia with one laboratory, Thailand and the Philip- pines with two laboratories each. The coordinator in this correlation programme is respon- sible in preparing the correlation samples and sending them by air to each participating laboratory. The first part of this programme (3rd Correlation Programme) was started by sending samples in January 1982 and the second part (4th Correlation Programme) was starting by sending samples in March 1982. It will appear in the next publication. After being tested by the participating laboratories, the test result are to be sent to the coordinator for the determination of the standard deviation and other statistical data. Based on these results, conclusions can be drawn about the deviation of laboratory test results and about outliers to be rejected. For better analysis of the results, for each of the samples for correlation it is also required to report physical and chemical tests such as specific gravity, R.V.P., distillation and lead (TEL) content in the receiving laboratories. This is necessary in order to take into account any possible changes in the sample properties which might have occured during transporta- tion and storage. Also to be observed are ambient and engine operating conditions during the correlation tests. The results of this analysis can then be used as a base for deviations the occurence of outliers and recommendation of remedial steps to be taken. d The method used for testing the samples is the bracketing method, while for rounding the value of the member found during the tests the ASA rules for rounding are used. SADIM The Grubb's rejection criteria with the use of